1994
DOI: 10.1161/01.str.25.4.782
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale and brain infarct. Echocardiographic predictors, recurrence, and prevention.

Abstract: Background and Purpose Paradoxical embolism through a patent foramen ovale is a recognized cause of stroke, but clinical predictors, recurrence rate, and prevention of brain infarcts in patients with patent foramen ovale have not been determined. We reviewed transesophageal echocardiographic records to ascertain echocardiographic predictors and optimal prophylaxis for patent foramen ovale-related infarcts.Methods A patent foramen ovale was identified in 74 patients during 615 transesophageal echocardiograms by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 17 publications
4
55
0
3
Order By: Relevance
“…Four studies have reported retrospectively on 86 patients treated nonrandomly with aspirin (a small number were also treated with warfarin). The weighted average recurrence rate is 6%/year [57][58][59][60]. In a different group of 86 patients treated nonrandomly with warfarin (a small undefined number were in reality treated only with aspirin), the recurrent stroke rate was slightly lower at 4.7%/year [57][58][59][60] (Fig.…”
Section: Patent Foramen Ovale (Pfo)mentioning
confidence: 99%
“…Four studies have reported retrospectively on 86 patients treated nonrandomly with aspirin (a small number were also treated with warfarin). The weighted average recurrence rate is 6%/year [57][58][59][60]. In a different group of 86 patients treated nonrandomly with warfarin (a small undefined number were in reality treated only with aspirin), the recurrent stroke rate was slightly lower at 4.7%/year [57][58][59][60] (Fig.…”
Section: Patent Foramen Ovale (Pfo)mentioning
confidence: 99%
“…Patients with documented PFO and previous embolic events are at increased risk for recurrent stroke of up to 4.2% per year, even in the context of therapeutic anticoagulation. [1][2][3][4] Percutaneous transcatheter closure is a potential option for patients with PFO and thromboembolic phenomena that avoids the morbidity associated with surgical closure or lifelong anticoagulation. 1 However, long-term data on the effectiveness of transcatheter PFO closure in stroke prevention are limited.…”
mentioning
confidence: 99%
“…9,10 Patients with PFO and paradoxical embolism are at increased risk of recurrent systemic thromboembolic events, ranging from 3.2% to 3.8% per year. [11][12][13][14] The optimal management of these patients remains controversial. Longterm anticoagulation, 11,12,15 surgical PFO closure, 16 -18 and percutaneous transcatheter closure of the PFO 19 -21 have been proposed as therapeutic options.…”
mentioning
confidence: 99%
“…[11][12][13][14] The optimal management of these patients remains controversial. Longterm anticoagulation, 11,12,15 surgical PFO closure, 16 -18 and percutaneous transcatheter closure of the PFO 19 -21 have been proposed as therapeutic options. Oral anticoagulation and surgical closure are associated with a significant morbidity and mixed results regarding stroke prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation